1980
DOI: 10.1042/bj1910203
|View full text |Cite
|
Sign up to set email alerts
|

Proteinase activity in chondroitin lyase (chondroitinase) and endo-β-d-galactosidase (keratanase) preparations and a method to abolish their proteolytic effect on proteoglycan

Abstract: Significant amounts of proteinase activity have been found in chondroitin ABC lyase (EC 4.2.2.4), chondroitin AC II lyase and endo-beta-D-galactosidase (keratanase) from commercial sources. It would appear, therefore, that certain earlier biochemical and histochemical studies, which employed these commercial enzyme preparations for their presumed ability to degrade only glycosaminoglycans, may require re-evaluation. A mixture of EDTA, N-ethylmaleimide, phenylmethanesulphonyl fluoride and pepstatin abolishes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(35 citation statements)
references
References 10 publications
0
35
0
Order By: Relevance
“…Aggrecan (2 mg) or G1-link protein-hyaluronan ternary complex was dissolved in 2 ml of 0.1M Tris acetate buffer, pH 7.0, containing protease inhibitors (24), and 100 pl chondroitinase ABC (2.5 units/ml) and 100 pI keratanase (5 unitdml) were added and the solution incubated overnight at 37°C. The sample was desalted on a Sephadex G-50 column equilibrated with 0.05M NH,HCO,, pH 8.0, v d freeze dried.…”
Section: Methodsmentioning
confidence: 99%
“…Aggrecan (2 mg) or G1-link protein-hyaluronan ternary complex was dissolved in 2 ml of 0.1M Tris acetate buffer, pH 7.0, containing protease inhibitors (24), and 100 pl chondroitinase ABC (2.5 units/ml) and 100 pI keratanase (5 unitdml) were added and the solution incubated overnight at 37°C. The sample was desalted on a Sephadex G-50 column equilibrated with 0.05M NH,HCO,, pH 8.0, v d freeze dried.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that the GAG digestion enzyme preparations may contain low levels of contaminating proteases, and the use of a protease inhibitor mixture is recommended to eliminate any effect by contaminants on sample integrity (30). The protease inhibitor mixture included during deglycosylation of samples following enzymatic assay could not be used in the preparation of the deglycosylated substrate because the presence of the mixture would interfere with aggrecanase and tMMP-3 enzyme activities.…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrating an interaction of a protein with the extracellular matrix (ECM) using bacterial glycosidases are often compromised by the potential contribution of protease contaminants that have been detected in the commercially available preparations (24). To eliminate the contribution of the contaminating proteases, all digestions using the glycosidases were done in the presence of a broad-spectrum protease inhibitor cocktail (Complete), which was purchased from Boehringer Mannheim (Indianapolis, IN).…”
Section: Methodsmentioning
confidence: 99%